The Role of Sustainability in WSP Group’s Long-Term Strategy and Competitive Advantage - Sirajuddin, Seema; Pande, Gaurav; Iskender, Khatira (2010)
Sustainability is a part of the global system, it is not an isolated section of any one of the entities within it. Globalization, despite its positive potential has contributed to immense social distress. The growth in population coupled with rising economic developments is primarily responsible for the progressive degradation of the earth's resources. The construction industry in particular is responsible for extracting materials directly from natural resources. A few engineering consultants like WSP are trying their best to mitigate some of its worst effects by providing end to end sustainable solutions, based on local regulations, requirements and standards, to their clients by replacing the legacy of non-sustainable infrastructure with increasingly more sustainable processes, systems and technologies.